1998
DOI: 10.1016/s0002-9440(10)65639-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Reduction in MRP-1/CD9 and KAI1/CD82 Expression with Recurrences in Breast Cancer Patients

Abstract: MRP-1/CD9, KAI1/CD82, and ME491/CD63, have been reported to be associated with the metastatic potential of solid tumors. The aim of this study was to determine whether their expression in tumor tissues is a useful indicator for prognosis in breast cancer patients. We studied 109 breast cancer patients who underwent surgery. Quantitative reverse transcription-polymerase chain reaction analysis was performed to evaluate the expression of these genes. The results were confirmed with immunohistochemistry. All of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
114
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(121 citation statements)
references
References 37 publications
5
114
1
1
Order By: Relevance
“…Ubiquitous expression of CD82 prompted others to explore the possibility that loss of expression may not be limited to the prostate. Loss or low expression has been shown to correlate with poor prognosis in lung (Adachi et al, 1996), pancreatic (Guo et al, 1996), breast (Huang et al, 1998), bladder (Yu et al, 1997), colon (Lombardi et al, 1999), esophageal (Uchida et al, 1999;Miyazaki et al, 2000), cervical (Liu et al, 2001), ovarian , and endometrial cancers. Downregulation of CD82 expression has also been observed in many metastatic tumor cell lines (White et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitous expression of CD82 prompted others to explore the possibility that loss of expression may not be limited to the prostate. Loss or low expression has been shown to correlate with poor prognosis in lung (Adachi et al, 1996), pancreatic (Guo et al, 1996), breast (Huang et al, 1998), bladder (Yu et al, 1997), colon (Lombardi et al, 1999), esophageal (Uchida et al, 1999;Miyazaki et al, 2000), cervical (Liu et al, 2001), ovarian , and endometrial cancers. Downregulation of CD82 expression has also been observed in many metastatic tumor cell lines (White et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…10 Loss of KAI1 expression is also associated with a poor prognosis in several cancer types 6,11,12 and breast cancer recurrence. 13 The role of KAI1 in prostate cancer progression has been studied by several groups; indeed KAI1 was initially proposed to be a prostate-specific metastasis suppressor. 1 While recent studies have provided some evidence that increased KAI1 expression might occur in early stage disease, 14 all studies thus far have shown that KAI1 mRNA and protein levels are dramatically reduced in advanced disease, as well as in lymph node metastases.…”
Section: Introductionmentioning
confidence: 99%
“…All of them were based on immunohistochemical analyses of a limited number of frozen breast cancer sections, because anti-KAI1 antibodies available at that time were not suitable for detection of KAI1 in larger series of formalin-fixed paraffin-embedded archival breast cancer tissue. 15,16 In addition, a number of studies concerning expression and function of KAI1 in breast cancer have been invalidated by the use of the misidentified cell line MDA-MB-435. 10,17,18 These cells have recently turned out to be M14 melanoma cells and are not informative on the biology of breast cancer.…”
mentioning
confidence: 99%